The regional distribution of spanish unemployment. A spatial analysis - Enrique Lopez-Bazo; Tomas Del Barrio; Manuel Artis (European Regional Science Association (ERSA), 2002)
This paper proposes a set of tools to analyse the regional distribution of unemployment. As we are interested in the characteristics of the whole distribution, we complement results from the traditional regression analysis with those from the estimation of its external shape before and after being conditioned to factors underlying regional unemployment. Besides, the paper explicitly addresses the spatial characteristics of the distribution, and the empirical model build to determine the explanatory factors includes spatial effects. We apply this framework to the study of the provincial distribution of unemployment rates in Spain in the mid-eighties and late nineties, when economic transformations could have caused different regional responses. Results point to increasing spatial dependence in the distribution of regional unemployment rates, and a change in the factors causing regional differentials over the last decade.
Keywords: 330